2019
DOI: 10.1530/rep-18-0581
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic effects of Shiga toxin-2 on human extravillous trophoblast cell lines

Abstract: Shiga toxin (Stx2) producing Escherichia coli infections during early gestation may impair placentation through a Stx2 damage of extravillous trophoblast (EVT) cells. We have previously demonstrated that Stx2 injected in rats in the early stage of pregnancy causes spontaneous abortion by a direct cytotoxic effect in the highly perfused feto-uteroplacental unit. The main aim was to evaluate the effects of Stx2 on EVT in order to understand the possible adverse effects that the toxin may have on trophoblast cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…In vitro studies using the WISH cell line derived from human amniotic tissue showed that both Stx1 and Stx2 induce apoptosis (Yoshimura et al 2002). Additionally, Stx2 impairs cell migration, invasion, and endovascular differentiation in extravillous trophoblast cells (Scalise et al 2019).…”
Section: Shiga Toxin-producing Escherichia Colimentioning
confidence: 99%
“…In vitro studies using the WISH cell line derived from human amniotic tissue showed that both Stx1 and Stx2 induce apoptosis (Yoshimura et al 2002). Additionally, Stx2 impairs cell migration, invasion, and endovascular differentiation in extravillous trophoblast cells (Scalise et al 2019).…”
Section: Shiga Toxin-producing Escherichia Colimentioning
confidence: 99%